Anthropometric Assessment of Neck Adipose Tissue and Airway Volume Using Multidetector Computed Tomography: An Imaging Approach and Association With Overall Mortality. Issue 45 (November 2015) - Maresky, Hillel S.; Sharfman, Zachary; Ziv-Baran, Tomer; Gomori, J.M.; Copel, Laurian; Tal, Sigal
Abstract : Abstract: Neck adiposity tissue volume (NATV) accumulation is an indicator for metabolic syndrome and cardiovascular disease (CVD). Neck circumference is a poor measure of NATV, and a quantifier for this entity has not yet been established. To evaluate volumetric quantification by multidetector computed tomography (MDCT) as a reproducible anthropometric tool to measure NATV and airway volume (AWV). A total of 519 patients, including a subset of 70 random patients who underwent head and neck CT scanning in our hospital within 1 year (2013), were studied. Included patients were all those undergoing nonenhanced CT (NECT) or CT angiography (CTA). Neck cross-sectional areas (NCSA) were measured at 2 separate levels of the neck, and 3D postprocessing tissue reconstruction was performed, and NATV and AWVs were quantified volumetrically for all patients within the year. The average NCSA at the level of the soft palate and thyroid cartilage was 22, 579 and 14, 500 mm 2, respectively. NATV when compared to the upper and lower levels of NCSA showed correlations of 0.64 and 0.79, respectively ( P  < 0.001). Interobserver analysis showed mean deviations of 0.46% and 0.32% for NATV and AWV, respectively. A strong correlation between NATV and body mass index (BMI) was found ( r  = 0.658, P  < 0.001), and the top quartile of NATV:AWV patients (out of 519 patients) displayed a statistically significant mortality rate during 670 days of follow-up (d = 7.5%, P  = 0.032). After adjustment for age and gender, the association between NATV:AWV and mortality was close to significant ( P  = 0.072). Volumetric quantification of NATV and AWV is a reproducible and prognostic anthropometric tool, as a high NATV:AWV demonstrated a significant risk factor for mortality; future research may further advance our understanding of this phenomenon.